Evaluation of genetic diversity between 11 banana cultivars (MUSA SPP.) by ISSR marker - SAIFULDEEN AHMED HASAN; SHAIK MAHAMMAD KHASIM (International Journal of Pharma and Bio Sciences, 2018)
Banana is a major food crop of India it belongs to the genus Musa. Its a staple food in the tropical and subtropical countries, and worldwide. It has great significance commercially as well as with regard to its nutritional value. The molecular marker studies are vital for determining the genetic variation in germplasm and also among genotypes in breeding programs. The aim of the present study is to evaluate the genetic diversity among 11 Musa genotypes cultivated in Andhra Pradesh using Inter Simple Sequence Repeats Marker. Eight ISSR primers were employed to study the genetic diversity among the 11 Musa genotypes. ISSR 4 primer generated the maximum number (14) of amplicons among the primers whereas ISSR 6 primer displayed better number of amplicons across all the samples. Monomorphic amplicons were produced by ISSR 9, ISSR 11 and ISSR 12 primers for all the Musa varieties. The UPGMA clustering method for ISSR 6 primer demonstrated the genetic diversity among the 11 Musa genotypes. The study concludes that ISSR marker is a valuable tool to study and differentiate the genotypes of Musa spp.